Implementasi Program DDC (Doa, Dhuha, Conversation) untuk Meningkatkan Kemampuan Multilingual Peserta Didik melalui Pendekatan Behavioristik - Irfani, Ranu Nada (Universitas Negeri Padang, 2025)
Foreign languages positively impact learning, especially in the current era of globalization. However, behind the positive impact of learning foreign languages, regional or local languages are being eroded and there are fewer speakers. Therefore, the world of education needs to pay balanced attention to language teaching, both regional, national, and foreign languages. In this regard, Madrasah Ibtidaiyah Sunan Pandanaran offers an activity program to improve the multilingual ability of its students, namely DDC, which was reviewed through a behavioristic approach in this study. Based on this explanation, this study aims to determine the DDC program to improve students' multilingual skills, which will be reviewed through a behavioristic approach. This study used descriptive quality research. The DDC program is implemented consistently every Monday to Thursday before class, learning by cycle. The implementation uses the Sam'iyah Syafawiyah method and the drill method, and the media used includes handbooks, templates, and posters. Conversation activities in the DDC program have fulfilled the principles of the behavioristic approach, including learning as a change in behaviour, stimulus and response, and reinforcement. Furthermore, the DDC program has also implemented a learning process according to a behavioristic perspective: learning by doing, learning from experience, and learning by trial and error.